A Preliminary Report on Cleft Deformities of the Face and associated Anomalies in Abha, Saudi Arabia - Togoo, Rafi A; Yaseen, Syed Mohammad; Meer, Zakirulla; AlMohy, Ahmad; AlQahtani, Jaber (Journal of Orofacial Research, 2012)
Cleft deformities of the face are one of the major congenital anomalies seen in our environment. There is a dearth of data from this major Southern city of Saudi Arabia on the incidence of the deformities and associated anomalies. This preliminary report aims to record the pattern of cleft lip/palate and associated anomalies at Aseer Central Hospital in Abha, Saudi Arabia. Materials and methods: A retrospective study was conducted at Aseer Central Hospital, Abha, to identify all cleft lip and palate patients that reported or were treated between 2005 and 2011. Cleft lip and/or palate records were obtained from patient’s files in Department of Maxillofacial Surgery, Pediatrics and Medical records. Gender of patient, type of cleft and any associated congenital anomalies/syndromes were recorded. Results: Of the patient records studied, 60% were patients male and 40% female. Isolated cleft palate was the most common at 60% followed by combined cleft lip palate at 24% and isolated cleft lip at 16%. Eleven percent of the patient’s studies showed associated anomalies with isolated cleft palate. Conclusion: The study concluded that isolated cleft palate cases are more common than other variants of orofacial clefts. The pattern of cleft observed in the current study was similar to reported studies for Arab populations. This preliminary report lays the foundation for large population and birth registry based studies for prevalence and frequency of orofacial anomalies in Saudi Arabia.